Description of Fezzan through the books of Muslim travelers and geographers (From the third century AH to the seventh century AH) (Journal of Human Sciences, 2021)
The One of the most important difficulties that a researcher faces in studying the history of Fezzan is the lack of resources and material that help him to move forward in his research, as undoubtedly the researcher driving by the material that he has to carry out his job.  Perhaps the most prominent thing that we notice when researching the history of the medieval Fezzan and its scarcity is the lack of information compared to other regions and neighboring in Egypt and the Islamic Maghreb, which have had many books that trace their history. On the other hand, Fezzan was mentioned and described in the books of Muslim travelers and geographers, and their writings. This represented a source of geographical and historical information through their transmission of their own observations or through their transmission from others who mentioned Fezzan before them. In fact most of these writings are much later than the stages that the region went through, such as the Arab conquest. The details of travelers and geographers wrote about Fezzan was written in late historical eras and conveyed to us sporadic, fluctuating and repeated sometimes. These information about Fezzan in particular and Libya in general, might not enough to write a solid study about Fezzan in the Islamic era. Perhaps the absence of independent states in the Fezzan region in particular and in Libya in general, similar to what happened in the rest of the Islamic Maghreb countries, is a reason for the reluctance of historians to write about Fezzan. Moreover, the location of Fezzan in the middle of desert with a small population may make a great influence on its history, even though Fezzan has played for many centuries as a linkage between North and South. The history of Fezzan is scattered in the folds of books, the collection and coordinate the history of Fezzan from these resources become very important it matter to fill this gap in Fezzan and Libya history.